Optimalisasi Teknologi Dalam Pembelajaran Komputer Akuntansi Pada Siswa dan Guru SMK di Dhamasraya - Elfitri Santi; Eka Rosalina; Syafira Ramadhea Jr.; Desi Handayani; Zulvitri zulvitri (Jurnal Abdimas: Pengabdian dan Pengembangan Masyarakat, 2023)
Over the past five years the development of technology has experienced rapid growth and development, including computerization in the field of accounting. With the use of technology, all financial management can be done quickly, precisely and accurately. One software that is widely used by small and medium industries that is used for bookkeeping financial statements of various types of companies is the accurate accounting application. This application in the future will be tested on vocational students in the form of a Skills Competency Test (UKK). UKK results for students will be an indicator of achieving graduation competency standards. Meanwhile, for stakeholders, the UKK results are used as a source of information on the competencies possessed by prospective workers. However, currently there are still many teachers and students who cannot operate the accounting application, including at SMKN 1 Pulau Punjung school. Therefore, the community service team of the accounting department of Padang State Polytechnic had the opportunity to visit SMKN 1 Pulau Punjung, Dhamasraya Regency, to carry out training and assistance to teachers and students, so that these students have the competencies expected by the industry. In addition, an evaluation was also carried out to see the extent of the increase in students' understanding and skills in optimizing the accurate accounting application in managing financial data after the training was given, so that the knowledge provided was truly useful and could be used even though this service activity ended.